Incorporation of silver nanoparticles and eucalyptus oil onto electrospun hemp/PVA nanofibres and their antibacterial activity - Mogole, Lebogang (Vaal University of Technology, 2021)
The world is continuously losing the battle against superbugs (resistant bacteria towards commonly used antibiotics), hence there is an urgent need to develop novel antibacterial agents. In this study, green synthesized silver nanoparticles (AgNPs) and eucalyptus oil, were incorporated into the polymer blend fibres of polyvinyl alcohol (PVA) and cellulose nanocrystals (CNC’s). Various techniques were used to characterize the AgNPs, PVA/CNC polymer fibres, and PVA/CNC incorporated with AgNPs/eucalyptus oil. The morphology of AgNPs synthesized using an increasing concentration of the Citrus sinensis peels (CSP) extract was obtained from transmission electron microscopy (TEM). AgNPs synthesized using 1 and 2 % m/v (CSP) were agglomerated and whereas those synthesized using 3 % m/v of the extract were spherical with an average particle size 10 ± 1.2 nm. UV/Visible absorption spectra for all the synthesized AgNPs exhibited a surface plasmon resonance (SPR) peak at around 400 nm which is a characteristic peak of silver. Significant shifts in the absorption peaks or maxima were observed to signify changes in the shape and size of the nanoparticles. Scanning electron microscopy (SEM) was used to study the morphology of the fabricated polymer fibres. The Addition of CNC’s to PVA resulted in an increase in fibre diameter due to an increase in viscosity of the solution. An increase in the concentration of silver nanoparticles and the eucalyptus oil in the PVA/CNC resulted in a decrease in fibre diameter due to an increase in conductivity of the material. The fibres with AgNPs were smooth while the ones with the eucalyptus oil were beaded. X-ray diffraction (XRD) showed the presence of the AgNPs in the polymer fibres and Fourier transform infrared (FTIR) showed the presence of the functional groups that are available in the eucalyptus oil. The antibacterial efficiency of the PVA/CNC incorporated with AgNPs, eucalyptus oil, and the mixture of AgNPs and the eucalyptus oil was investigated using S. aureus and K. pneumoniae. All the materials showed significant inhibition of the growth of the selected bacterial strains. PVA/CNC polymer fibres incorporated with AgNPs showed higher antibacterial activity compared to PVA/CNC polymer fibres incorporated with eucalyptus oil.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Silver nanoparticles; Eucalyptus oil; PVA/CNC polymer fibres; Antibacterial activity; Polymer fibres; Dissertations, Academic -- South Africa.; Nanostructured materials.; Nanoparticles.; Antibacterial agents.; Drug resistance in microorganisms.